THE EFFECT OF TEAMS “KNOW-WANT-LEARN” STRATEGY ON STUDENTS’ ACHIEVEMENT IN READING DESCRIPTIVE TEXT - Putri Sri Rezeki Siregar; Sumarsih (Universitas Negeri Medan, 2015)
The aim of this study is to discover the effect of applying Teams “K-W-L” strategy in reading descriptive text. Experimental research design is used as the research method. This research took place at SMP N 1 SIANTAR NARUMONDA. There were 2 classes chosen as the sample with 30 students in each class. The classes were divided into two groups namely experimental and control group. The experimental group was taught by using Teams “K-W-L” strategy and control group was taught by using conventional method. The instrument was used to collect the data was a set of multiple choice tests, which was divided as pre-test and post-test. The result showed that t-test was higher than t-table (4,53 > 2,00) at the level of significant 0,05 with degree of freedom (df) 58. It means that hypothesis alternative (Ha) is accepted which show that Teams “K-W-L” strategy significantly effected on the students achievement in reading descriptive text. It was proved since mean score of experimental group is 74,83 higher than mean score of control group is 63,33. So, English Teacher are suggested to use Teams” know-want-learn” Strategy in order to improve students’ achievement in reading descriptive text.